Evolution of the Bacillus Calmette–Guerin Scar and Its Association with Birth and Pregnancy Characteristics in a Prospective Cohort of Infants in Iquitos, Peru - Schiaffino, Francesca; Lee, Gwenyth O.; Paredes-Olortegui, Maribel; Cabrera, Lilia; Penataro-Yori, Pablo; Gilman, Robert H.; Kosek, Margaret N. (American Journal of Perinatology, 2019)
Background Bacillus Calmette–Guerin (BCG) scar formation is considered a visual marker of vaccination and cell-mediated immune response. This study characterized the association between pregnancy and birth characteristics with BCG scar formation.Study Design Pregnant women were enrolled prospectively. Infants were followed up for the first 6 months of life, and the diameter of the BCG scar was recorded. Marginal models were fitted to assess the association of BCG scar diameter with pregnancy and birth characteristics using linear regressions with generalized estimating equations.Results A total of 307 infants were enrolled, of whom 19.2% (59/307) were of low birth weight. Among those with known gestational age, 7.1% were preterm births (21/295). Overall, 98.7% (303/307) of infants developed a BCG scar. BCG scar trends in a tropical environment, such as the Amazon, differ from the trends evidenced in the capital of Peru. For every additional week of gestational age, the mean scar diameter increased by 0.1 mm (95% confidence interval [CI]: 0.02, 0.24; p = 0.017). Maternal illness during pregnancy impacted BCG scar size, as the infants of mothers who self-report fever had a smaller scar diameter (1 mm, 95% CI: 0.5, 1.8 mm; p = 0.001).Conclusion The immune reaction to the BCG vaccination is affected by gestational age at birth and systemic inflammatory episodes during pregnancy.
Keywords: Bacillus Calmette–Guerin; preterm births; tuberculosis; Peru